Laparoscopic versus open resection for unfavorable sites gastric gastrointestinal stromal tumors: a propensity weighted cohort study - Yang Zong; Yawei Qian; Jianghao Xu; Qingya Li; Linjun Wang; Li Yang; Hao Xu; Jianfeng Gu; Zekuan Xu (BMC Surgery)
Abstract Background and objectives To compare the efficacy and feasibility of laparoscopic resection with those of open surgery for gastric gastrointestinal stromal tumors (GISTs) in unfavorable locations using the propensity score weighting (PSW) method. Methods Clinicopathological and follow-up data from 170 patients found to have gastric GISTs in unfavorable locations from January 2017 to December 2021 were analyzed retrospectively. Among the 170 patients, 121 underwent laparoscopic surgery, and 49 underwent open surgery. The PSW was used to create balanced cohorts and adjusted for six clinically validated covariates: sex, age, BMI, tumor size, mitotic rate, and recurrence risk. Results After PSW, 325.2 patients, consisting of 167 laparoscopic (Lap group) and 158.2 open surgery (Open group) patients, were matched. The Lap group had shorter operation times (84.7 ± 37.7 min versus 123.4 ± 46.9 min, P < 0.001) and shorter hospital stays (7.0 [5.0, 8.0] days versus 9.0 [8.0, 11.0] days, P < 0.001) than the Open group. Although the Open group exhibited a numerically higher complication rate (10.24% vs. 4.97%), this difference did not reach statistical significance (P = 0.243). Moreover, no significant differences existed in recurrence-free survival or overall survival. Conclusions Laparoscopic surgery is safe and feasible for gastric GISTs in unfavorable locations. Compared with open surgery, laparoscopic resection facilitates faster postoperative recovery and has a similar long-term prognosis.